The Dynamics of Student Knowledge Creation through SECI: A Qualitative Exploration in the Indonesian Context - Masduki Asbari; Danish Akbar Firdausy Asbari (Yayasan Aya Sophia Indonesia, 2025)
This study aims to analyze the implementation of the SECI model (Socialization, Externalization, Combination, Internalization) in the process of knowledge creation among higher education students in Indonesia. The SECI model, developed by Nonaka and Takeuchi, is an important framework in managing tacit and explicit knowledge in organizations, including higher education institutions. Through a descriptive qualitative approach, data were collected through structured in-depth interviews, participatory observation, and documentation at several public and private universities in Indonesia. The results showed that the socialization process more often occurs informally through interactions between students, while the externalization process occurs when students express ideas in assignments and discussions. The combination process appears in collaborative activities such as group work and research, while the internalization process is driven by direct learning experiences and practices. Academic culture, lecturer support, and digital infrastructure proved to be the main supporters of the success of the SECI model on campus. This research confirms the importance of SECI-based knowledge management in shaping students' innovative capabilities and suggests strategies for integrating SECI in the curriculum and extracurricular activities.